The Role of Clinical Evaluation in the Era of Cerebral Reperfusion - Tran Duc Anh; Duong Dang Hoa, Doan Quoc Hoai Phuong (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2020)
The role of clinical evaluation in the diagnosis and treatment of acute ischemic stroke remains unclear in current guidelines. The manifestations of stroke are diverse, leading to different approaches for evaluation and treatment for each patient. This article reviews the importance of neurological examination in diagnosing and treating acute stroke, particularly focusing on the identification of large vessel occlusions, posterior circulation stroke, intracranial artery stenosis, and the expansion of the therapeutic window for patients who arrive late to the hospital.